Artificial Intellegence In The Future Of Iraqi Healthcare System: Kecerdasan Buatan Di Masa Depan untuk Sistem Layanan Kesehatan Irak - Murad, Hayder (JOINCS (Journal of Informatics, Network, and Computer Science), 2024)
The expansion of healthcare AI in Iraq highlights the growing necessity for AI education among medical students. The aim of this research is to explore the perspectives of medical students in Iraq regarding artificial intelligence (AI), including their understanding of AI and their career aspirations. Methodologically, a group of Iraqi medical students were invited to participate in an anonymous electronic survey. The results indicate that a total of 318 responses were collected from 22 medical colleges. The majority of respondents (91.5%, s = 291) hold the belief that AI will have a significant impact on healthcare in the future. Specifically, their responses were categorized as strongly agreeing (33.6%, s = 107) or agreeing (57.9%, s = 184). This research reveals that Iraqi medical students recognize the significance of AI and are enthusiastic about engaging with this technology. Moreover, it suggests that there is a need to expand and enhance medical college training on AI to ensure that future healthcare professionals are well-prepared in this domain.